A restauração conservadora da filosofia: o Instituto Brasileiro de Filosofia e a autocracia burguesa no Brasil (1949-1968) - Gonçalves, Rodrigo Jurucê Mattos (2016)
In our thesis, we start from the historical reconstruction of bourgeois autocracy in Brazil and the development of class society after 1930. From this historical perspective of autocratic developments as renovation, that is, as a constant rearrangement and update of the structural power of the ruling class, reconstituting the formation of the University of São Paulo, after 1934 as a project of the São Paulo‟s oligarchy, and the Brazilian Institute of Philosophy (IBF – the acronym in Portuguese) from 1949 as a program of some sectors of autocratic intelligentsia. The IBF was the entity responsible for the publication of the Brazilian Magazine of Philosophy (RBF – the acronym in Portuguese), which is our main research‟s source. Aiming at a critical questioning of our object (the IBF and RBF), rescued the concept of philosophical hegemony apparatus (AHF), which allowed us to elucidate the IBF‟s contribution to the formation of an autocratic ideology. The main contribution came from São Paulo‟s renowned jurist, Miguel Reale, leader and founder of the Institute. Known to have belonged to the “movimento integralista” (a fascista movement), Reale will provide new ideology of the ruling class after the decline of fascism and with the defeat of fascists regimes in the mid 40‟s. In the Philosophy of Law (1953) book, the jurist will finalize the so-called "three-dimensional theory of law", which, however, has a number of formulations in order to exploit the ruling class with an authoritarian legal ideology. Later, in the early 60‟s, when Brazil was at the culmination of a general crisis, which was reflected in the economy, society, politics and culture, Reale publish two political works: Brazilian parliamentarianism (1962) and Pluralism and Freedom (1963). In these books the author will refine the borders of democratic liberalism, together with authoritarian-legal formulations of 50‟s, will give life to an autocratic ideology that will thrive as one of the most important formulations of the brazilian autocratic intelligentsia. With the 1964‟s coup and the military dictatorship, the brazilian ruling class completes its historical maturity, putting its decision as a major factor in external relation to the central powers of capitalism and, internally, to social classes dominated. This historical maturation occurred, however, with the decisive ideological contribution of IBF leader who, in turn, widely developed autocratic ideology inside the AHF that, together with the RBF, was the locus of expansion, discussion and propagation of that thought.